Avian influenza H9N2-specific changes in the adaptive immune receptor repertoire of Gallus gallus domesticus following vaccination and infectious challenge - Dascalu, S (2023)
Avian influenza viruses cause major losses to the poultry sector each year and also pose a significant risk for cross-species transmission to humans, where the disease manifestations can be very severe. However, within avian hosts, there is still a limited understanding of the adaptive immune system in the contexts of both health and disease, and the immunological mechanisms which underpin vaccine-induced protective responses against infectious challenge with pathogens such as avian influenza. As the ability of the adaptive immune system to recognise specific antigens is dependent on the T and B cell receptors which together comprise the adaptive immune receptor repertoire, understanding the determinants which shape its specificities and diversity is paramount for both improving our knowledge of the avian immune system and improving current prevention and control strategies such as vaccination. In this thesis, I present a comprehensive analysis of the domestic chicken (Gallus gallus domesticus) adaptive immune receptor repertoire upon infection and/or vaccination with H9N2 avian influenza – a pathogen that is widely prevalent across the world and poses significant risk both to the poultry sector and to human health and wellbeing. At the time of writing, no published research has examined the avian adaptive immune repertoire using high throughput sequencing, and no repertoire studies have been performed in birds that were infected with and/or vaccinated against avian influenza. My analyses thus provide valuable information on the avian adaptive immune system and the impacts of H9N2 infection and/or vaccination on the avian adaptive immune receptor repertoires.